2013
DOI: 10.1017/s1041610213000203
|View full text |Cite
|
Sign up to set email alerts
|

Sense of coherence, burden, and affective symptoms in family carers of people with dementia

Abstract: Carers reporting high levels of anxiety and depression are more likely to report low levels of sense of coherence. The relationship between stress related to caregiving and depressive symptoms is mediated by carers' self-reported sense of coherence. Future psychotherapeutic intervention studies in family carers of people with dementia may incorporate strategies that specifically target sense of coherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 55 publications
1
47
0
Order By: Relevance
“…To our knowledge, four studies have examined SOC among caregivers for individuals with dementia . In 2008, Andrén and Elmståhl revealed that caregivers with a lower caregiver burden had significantly higher SOC scores than those with a higher burden.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, four studies have examined SOC among caregivers for individuals with dementia . In 2008, Andrén and Elmståhl revealed that caregivers with a lower caregiver burden had significantly higher SOC scores than those with a higher burden.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Orgeta and Sterzo reported that caregivers with a low SOC are more likely to report high levels of depression and anxiety. They emphasized the need to for psychotherapeutic interventions that target the enhancement of SOC for familial caregivers of people with dementia . In a randomized controlled trial, Langeland et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carers' perceived control of a stressful situation was found to significantly impact on carers' burden and depressive symptoms . One study reported a significant negative correlation between sense of coherence and carer outcomes, including stress, anxiety, and depression. Välimäki and colleagues reported that higher levels of depression predicted a decreased sense of coherence over time.…”
Section: Psychological Dimensions Of Caringmentioning
confidence: 99%
“…Objective burden assesses both negative and upsetting experiences while subjective burden focuses on perceptions of distress over particular experiences. Burden may affect how caregivers interact with others, as well as other roles they assume outside their home [8]. Caregiver burden has been associated with poorer mental health and worse physical health outcomes; and where caregiver’s mental health declines, it may result in their relative’s self-neglect and diminished quality of care [9].…”
Section: Introductionmentioning
confidence: 99%